Stress response in pathogenic bacteria [ - Kidd, Stephen P. (Advances in molecular and cellular microbiology, 2011)
The ability of pathogenic bacteria to adapt to various chemical, biochemical and physical conditions within the human host and their ability to respond to stresses generated in these environments is a central feature of infectious diseases and the outcoe of bacterial infection. This book covers the key aspects of this rapidly developing field, including the generation of stresses by the host immune system, bacterial response to reactive chemicals, and adaptation to environmental conditions of anatomical niches such as the gut, mouth and urogenital tract. It also addresses the increasing impor.